2019
DOI: 10.1007/s00701-019-03804-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between medical academic genealogy and publication outcome: impact of unconscious bias on scientific objectivity

Abstract: Background: Our previous studies suggest that the training history of an investigator, termed "medical academic genealogy", influences the outcomes of that investigator's research. Here we use meta-analysis and quantitative statistical modeling to determine whether such effects contribute to systematic bias in published conclusions. Methods: 108 articles were identified through a comprehensive search of the high-grade glioma (HGG) surgical resection literature. Analysis was performed on the 70 articles with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…They also reported that neurosurgical publications more often tend to support maximal resection than publications by radiation oncologists or medical oncologists [10]. In the present article, based on the same review of the same 108 American glioma papers, the authors (or nearly the same authors) now quantify the previously reported impact of genealogy on publication results in some greater detail [11]. However, the difference from their previous work is marginal.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…They also reported that neurosurgical publications more often tend to support maximal resection than publications by radiation oncologists or medical oncologists [10]. In the present article, based on the same review of the same 108 American glioma papers, the authors (or nearly the same authors) now quantify the previously reported impact of genealogy on publication results in some greater detail [11]. However, the difference from their previous work is marginal.…”
mentioning
confidence: 57%
“…Hirshman and colleagues performed a systematic review of publications by American authors that have reported on the survival effect of gross total surgical resection in patients with high-grade gliomas. They identified 108 scientific papers and now publish their fourth paper based on this review of the American glioma literature [11]. Internet searches were performed to determine the authors' medical subspecialty as well as the timing and location of their medical school, residency, and fellowship training.…”
mentioning
confidence: 99%
“…This should be kept in mind when reading, reviewing, or conducting meta-analyses of the literature in many fields of medicine, especially when relying on low-level evidence. The present review study adds to the recent work addressing how medical genealogy may affect study results and publication patterns [ 11 13 ]. The authors of these studies have introduced the term “genealogy bias.”…”
Section: Discussionmentioning
confidence: 99%
“…Academic genealogy is the linking of scientists who have been academic mentors for each other and has been used to demonstrate the influence of mentors on students in several other fields [ 2 , 22 ]. Recently, academic genealogy was used to review patterns in American publications on the survival effect of gross total surgical resection in patients with high-grade gliomas [ 11 ]. It was found that researchers belonging to different genealogies (e.g., neurosurgeons vs. radiation-oncologists) tend to reach contradictory findings and publish in different journals.…”
Section: Introductionmentioning
confidence: 99%
“…More than a third of the trials found a difference between operative and non-operative treatment, but in less than 4% non-operative management was found to be superior. However, most trials were conducted by surgeons, and this can be a source of bias as the genealogy of scientist may have an impact on their findings [8]. Further, high JADAD score, reflecting better methodological quality [10], was associated with lower chance of demonstrating a benefit from surgery.…”
mentioning
confidence: 99%